PENGARUH PEMBERIAN POSISI ALIH BARING TERHADAP PENCEGAHAN KEJADIAN DEKUBITUS PADA PASIEN STROKE DI RS KALOORAN AMURANG - Rantung, Riana; Nindi, Engryne (Journal Of Community & Emergency, 2024)
The management of the bed transfer is done to reduce too long pressure and frictional force against the skin. In addition, change position to prevent the occurrence of decubitus by giving positions every 2 hours. Giving over the beds has the opportunity to reduce the pressure and friction force on the skin. So as to prevent the occurrence of decubitus (Effendi, 2011). The purpose of this study is known to be the Effect of Giving a Baring Transfer Position on the Prevention of Decubitus Events in Stroke Patients at Kalooran Amurang Hospital. The type of research used is research using experimental methods with quasy experimental design research rangan and using a post test only control group design approach. The population in this study, namely patients with a diagnosis of stroke who were temporarily treated at Kalooran Amurang Hospital, amounted to 18 people. The data was analyzed using a statistical-test test with a utilization rate of 95% (α): 0.05. Based on sig value. Levene's Test is 0.567 > 0.05 so it can be interpreted that the data variant between the experimental group and the control group is homogeneous or the same. Based on the value of Sig. (2-tailed) of 0.022 < 0.05 then it was concluded that H0 was rejected and Ha was accepted. Thus it can be concluded that there was a significant difference between the average risk of decubitus events in the experimental group given the position of the bedover and the control group that was not given the intervention. The conclusions in this study are to show that the occurrence of decubitus after being given a position of dising in the experimental group is known to be mostly in the small category of occurs. The distribution of decubitus events without being given a position over the lie in the control group is mostly in the category of possibility of occurring. There is a significant influence on the provision of the position of the bedover to the prevention of decubitus events in stroke patients at Kalooran Amurang Hospital.